Education Workspace Application (EWA) Mobile App for Managing the Students Information Developed By Java - S, Dhivya; Jancy, Merlin; Kumaran, Arul; pandian, Arun; Bhuvaneswaran, Bhuvaneswaran (International Journal of Computer Sciences and Engineering, 2022)
In today’s environment technologies play a vital role. Nowadays college and school students require new and smart technology like smartphones which supports to get information related to applying for leave or OD, information about placement, attendance percentage etc. Though there are online tools like Google classroom which supports students and teachers by some facilities like to access lecture notes, quizzes, assignments, etc. But Google classroom does not support features like accessing information about their leave/OD, attendance percentage, no due, semester results, and other details.Maintaining the records of the university/school is becoming an aberration. The authorities/admin spend adequate time to maintain this records of the students .Not only the authorities but, even students spend most of their time for doing their regular and basic activities.This project provides a better way which eradicates the usage of paper .A mobile app which has all the facilitates through we can access of all academic-related details of the students and teachers.